DEM-continuum mechanics coupled modeling of slot-shaped breakout in high-porosity sandstone. (April 2020) - Wang, Tuo; Huang, Hongwei; Zhang, Fengshou; Han, Yanhui
Highlights: Simulate the slot-shaped breakout based on a 3D DEM-continuum coupled model. Reveal the formation of slot-shaped breakout due to particle crushing and removal. Reveal the formation of compaction band after the breakout length ceases to grow. Study the effects of different parameters on the length of slot-shaped breakout. Abstract: Mechanism for slot-shaped borehole breakouts observed from drilling experiments in high-porosity sandstone is investigated using the hybrid DEM-continuum mechanics modeling approach. The rock material in DEM is modeled as an assembly of particles with flat joints at contacts. The failure mechanism for the slot-shaped breakout is mainly attributed to particle crushing, which is different from the conventional dilatant V-shaped breakout where shear failure plays the primary role. The damage evolution of the slot-shaped breakout can be divided into three stages, i.e., breakout initiation induced by the stress concentration near the excavated borehole, formation and propagation of the slot-shaped borehole breakout as a result of particle crushing and removal, and formation of a compaction band at the tip of the breakout when the breakout length ceases to grow. The dynamic change of stress during the breakout slot extension is modeled. The continuous particle breakage at the tip of the breakout maintains the same level of stress concentration as the breakout propagates. The majority of the particle loss is caused by the particle crushing and subsequent removal. The evolution of microcrack strike suggests change of the preferential failure orientation from approximately parallel to the maximum horizontal stress direction to forming a small angle to the minimum horizontal stress direction. Parametric studies show that increasing the horizontal stress anisotropy, broadening the range of particle size, and increasing the rock porosity will all increase the length of the slot-shaped breakout. The normalized breakout length tends to increase with the increase of borehole size before reaching a stable value.